Verifiably private outsourcing scheme for multivariate polynomial evaluation - Yan-li REN; Da-wu GU; Jian-xing CAI; Chun-shui HUANG (Tongxin xuebao)
With the development of cloud computing and big data,it had important practical significance for how to outsource private data and verify the computing result efficiently.A verifiably outsourcing scheme for multivariate polynomial evaluation based on multilinear maps and homomorphic encryption was proposed where the user could verify the computing result exactly.The proposed scheme is provably secure without random oracles and the multivariate polynomial itself and the input of the function are private for the server.Moreover,the cost of the user is much smaller than that of the server,and it is much smaller than that of computing the multivariate polynomial directly.